Chemical composition, seasonal variation and antiaging activities of essential oil from Callistemon subulatus leaves growing in Egypt - Omyma Rabie; Heba A. S. El-Nashar; Taghreed A. Majrashi; Tarfah Al‐Warhi; Mahmoud A. El Hassab; Wagdy M. Eldehna; Nada M. Mostafa (Taylor & Francis Group, 2023)
Callistemon is an aromatic genus of flowering plants belonging to family Myrtaceae. The essential oils of C. subulatus leaves were collected in four seasons and analyzed using GC/MS. The oils demonstrated monoterpenes as the predominant class. Eucalyptol was the main component in all seasons; summer (66.87%), autumn (58.33%), winter (46.74%) and spring (44.63%), followed by α-pinene; spring (31.41%), winter (28.69%), summer (26.34%) and autumn (24.68%). Winter oil, the highest yield (0.53 mL/100g), was further investigated for its inhibitory activity against enzymes associated with ageing; elastase and acetylcholinesterase. It remarkably inhibited elastase and acetylcholinesterase with IC50 values of 1.05 and 0.20 µg/ml, respectively. A molecular docking study was conducted for the major oil components on the active sites of target enzymes. Eucalyptol revealed the best binding affinity for both enzymes. C. subualtus oil could be used as supplement for management of ageing disorders like skin wrinkles and dementia.